2018
DOI: 10.17244/eku.466812
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Respect for Diversity Program with Family Involvement on 5 and 6 Year Old Children Respect for Diversity

Abstract: Programının" çocukların farklılıklara saygı düzeyine etkisinin incelemektir. Yapılandırmacı yaklaşım temel alınarak hazırlanan "5-6 Yaş Grubu İçin Geliştirilen Aile Katılımlı Farklılıklara Saygı Programı" haftada 3 gün her güne birer tane olmak üzere toplam 52 adet bütünleştirilmiş etkinlikten oluşmaktadır. Araştırma nicel bir çalışmadır. Deneysel modellerden ön test-son test kontrol gruplu model kullanılmıştır. Araştırmanın çalışma grubunu 2015-2016 eğitim ve öğretim yılı bahar döneminde İstanbul ilinin Kadık… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
0
0
3
Order By: Relevance
“…Consequently, it appears that the level of tendency of the students in the experimental group related to showing respect increased significantly after the activity-based practices. Such results also support the findings of similar studies found in the relevant literature (İşcan, 2007;Keskinoğlu, 2008;Öztürk, 2018;Polat & Yıldız, 2018;Banks, 2019).…”
Section: Results Discussion and Conclusionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consequently, it appears that the level of tendency of the students in the experimental group related to showing respect increased significantly after the activity-based practices. Such results also support the findings of similar studies found in the relevant literature (İşcan, 2007;Keskinoğlu, 2008;Öztürk, 2018;Polat & Yıldız, 2018;Banks, 2019).…”
Section: Results Discussion and Conclusionsupporting
confidence: 91%
“…Benzer şekilde Banks (2019), çokkültürlü eğitimin öğrencilerin saygı düzeylerinde olumlu bir etki yarattığını belirtmiştir. Yine Polat ve Yıldız (2018), okulöncesi dönemi çocuklarına uyguladıkları farklılıklara saygı programının, öğrencilerdeki farklılıklara saygı düzeyine etkisini incelediği çalışmasında, deney grubu öğrencilerinde saygı düzeylerinde anlamlı bir artış olduğunu bulmuştur. İşcan (2007) ve Keskinoğlu (2008) da ilköğretim öğrencilerine uygulanan etkinlik temelli değerler eğitimi programının, öğrencilerin ahlaki olgunluk düzeylerine olumlu etkisi olduğunu belirlemişlerdir.…”
Section: Tartışma Ve Sonuçunclassified
See 1 more Smart Citation
“…Therefore, children's interaction with teachers and adults is at the heart of anti-bias education (Derman-Sparks and Edwards, 2010). Research shows that practices based on anti-bias education help both teachers and children to realize their identity, develop cultural awareness, and work on other personal features; in addition, it allows children to show positive attitudes towards differences (Simangan, 2012;Polat and Özkabak-Yıldız, 2018;Üner, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Çok kültürlü eğitim, önceden belirlenmiş özel bir müfredat değil, eğitim ve öğretimin her aşamasındaki karar ve uygulamalara yansıyan bir perspektiftir. Bu süreçte öğretmenlerin açık ve gizli olarak hangi sosyal bilgileri aktardıkları önem kazanmaktadır (Polat ve Özkabak-Yıldız, 2018;Ramsey, 1987).…”
unclassified